Analysis of feeding systems under urban and peri-urban livestock production of Deccan plateau - BIRADAR, NAGARATNA; SRIDHAR, K; PUSHPA, P; HANCHINAL, S N (The Indian Journal of Animal Sciences, 2010)
A study of 140 resource-poor urban peri-urban livestock keepers was carried out in 2007 in three tier-II cities, viz. Hubli-Dharwad, Belgaum and Bagalkote of Karnataka. In a randomized block design, their daily livestock feeding pattern was analysed by measuring actual quantities of feed and fodder fed to the livestock for 1 week in 15 households. Distance of the households from the centre of the city was used to separate blocks as ‘core’ (< 2 km), ‘fringe’ (2–4 km) and ‘more rural’ (4–8 km). Dependence on dry fodder was to the extent of 72% and it varied significantly across 3 groups. There was a significant difference in the quantity of dry fodder purchased by the livestock holders of three groups. Wheat bran and/or rice bran were the most sought after feed type as they were purchased in more quantity. The feeding system followed in non lactating livestock, that differed significantly, adequately met TDN but not DCP requirement. In lactating livestock it was deficit both in TDN and DCP. Highly significant difference was found both for meeting TDN and DCP requirement by the feeding system followed by the livestock holders of three categories. However, livestock husbandry still continues to be the main livelihood source for ‘core’ (40.75%) and ‘fringe’ (48.05%) groups. It is important to augment this livelihood source through technical and extension back-up on simple tools like cost